3D printing effect on the compressive strength of concrete structures. (7th November 2022) - Aramburu, A.; Calderon-Uriszar-Aldaca, I.; Puente, I.
Highlights: Mechanical behaviour of 3D printed shapes. Methodology that characterizes the mechanical properties of 3D printed specimens. Formula for calculating the effective area of 3D printed specimens. Abstract: The mechanical behaviour of annular 3D-printed cylindrical specimens is studied in this paper and compared to the expected theoretical behaviour of cast-moulded geometries. First, the compressive performance of the material as per standard EN 12390-3 is presented. The theoretical estimation differed from the test results and the reasons have been verified. Two key procedures are proposed by measuring the 3D-printed shapes: a geometrical characterization, in which both the material and the process parameters are considered, and a suitable formulation for defining the effective section of the printed geometries. The aim is to establish corrections for structural calculations, considering the material and the 3D printing process on the basis of the proposed guidelines and the test specimens.